Influence of Riverbed Pre-excavation on Local Scour of Pile Foundation Upstream of Cofferdam - LIU Congcong; LIN Hongxing; ZHAO Dongliang; CHAI Yuanfang (Renmin Zhujiang)
The scour of pile foundation is closely related to the coupling action of water flow and sediment,and the local scour depth directly affects the safety and stability of the structure.Taking the deep-water foundation of a bridge as the research object,this paper constructs and verifies a three-dimensional numerical sediment transport model to quantitatively analyze the flow and sediment movement rules of cofferdam and upstream pile foundation under the conditions of riverbed with and without pre-excavation.The results show that:the flow velocity at the upstream face of cofferdam is small,and that at the right angle of the cofferdam reaches the maximum.The back-row pile foundation is obviously affected by the wake of the front-row pile foundation and the reverse flow formed by the backwater of the downstream cofferdam.Under the condition of riverbed pre-excavation,the flow velocity around the cofferdam decreases,and the grooving is conducive to the backflow formation of the downward flow,and the weakening of sediment carrying capacity.Under the pre-excavation condition,the local flow velocity and scour depth of the upstream pile foundation decrease to different degrees,especially for the back-row pile foundation,with maximum local scour depth reduction of 82.86%~85.07%.